Pemberdayaan Wakaf Produktif Terhadap Pertumbuhan Ekonomi Masyarakat Di Kabupaten Maros - Khaerul Rasyidi,; Misbahuddin,; Saleh Ridwan, (Tasamuh: Jurnal Studi Islam, 2024)
This research aims to explore productive waqf on community economic growth in Maros Regency. This type of research is qualitative with a case study approach. The scientific approach used is shar'i-juridical. The informants in this research are the Ministry of Religious Affairs of Maros Regency and the Maros community itself. The techniques used in collecting data are observation, interview, and documentation. Data were processed through stages such as reduction, display, and verification. The results of the research show that: 1) The productive waqf empowerment system in Maros Regency will be effective if public legal awareness regarding the implementation of productive waqf is considered an awareness of the legal subject as a whole. Waqf management requires adequate human resources, so as to produce good quality work, professionalism, and responsibility in carrying out their duties to help the community's economy. 2) Productive waqf empowerment in Maros Regency is influenced by management effectiveness, appropriate asset selection, partnership cooperation, human resource development, wise financial management, and understanding of waqf principles. 3) The strategy to increase the legal awareness of the Maros community towards productive waqf management is through counseling or seminars, cooperation with religious institutions, provision of educational materials, practical training, and collaboration with the government and financial institutions.